An in vitro comparison of tibial tray cementation using gun pressurization or pulsed lavage - Schlegel, Ulf J.; Püschel, Klaus; Morlock, Michael M.; Nagel, Katrin (International orthopaedics, 2014)
Aseptic loosening of the tibial component remains a limitation to the highly successful procedure of total knee arthroplasty (TKA). Pulsed lavage improves bone cement penetration and interface strength in tibial tray cementation. This study tested whether pressurized cement application with a cement gun can compensate the use of jet lavage for bone surface preparation.
Gesehen am 07.09.2020